PRPF4 is a novel therapeutic target for the treatment of breast cancer by influencing growth, migration, invasion, and apoptosis of breast cancer cells via p38 MAPK signaling pathway. (October 2019) - Park, Song; Han, Se-Hyeon; Kim, Hyeon-Gyeom; Jeong, Jain; Choi, Minjee; Kim, Hee-Yeon; Kim, Min-Gi; Park, Jin-Kyu; Han, Jee Eun; Cho, Gil-Jae; Kim, Myoung Ok; Ryoo, Zae Young; et al.
Abstract: Pre-mRNA processing factor 4 (PRPF4), a core protein in U4/U6 snRNP, maintains snRNP structures by interacting with PRPF3 and cyclophilin H. Expression of the PRPF4 gene affects cell survival as well as apoptosis and is responsible for retinitis pigmentosa (RP). Proteomics analysis shows that PRPF4 may be a therapeutic target in human cancers. Nevertheless, the exact function and role of the PRPF4 gene are unclear. In this study, we assessed the expression of PRPF4 gene in human breast cancer cells. First, we confirmed that the PRPF4 gene was overexpressed in various breast cancer cell lines. Next, using breast cancer cell lines MCF7 and MDA-MB-468, we established stable cell lines with PRPF4 gene knockdown. We also performed microarray analysis to investigate molecular mechanisms underlying PRPF4 activity. All cell lines with PRPF4 gene knockdown exhibited reduced cell proliferation, remarkable reduction in anchorage-independent colony formation capacity, and reduction of PCNA protein, which is a marker cell of proliferation. Reduced expression of the PRPF4 gene induced apoptosis and changes in the expression of associated apoptotic markers in breast cancer cell lines. Knockdown of the PRPF4 gene reduced cellular capacity for migration and invasion (the key hallmarks of human cancers) and decreased the expression of genes involved in epithelial-mesenchymal transition (EMT). Microarray results showed that the expression of PPIP5K1, PPIPK2, and YWHAE genes was reduced at the transcriptional level, leading to reduced phosphorylation of p38 MAPK. These findings suggest that knockdown of PRPF4 gene slows down breast cancer progression via suppression of p38 MAPK phosphorylation. In conclusion, the PRPF4 gene plays an important role in the growth of breast cancer cells and is therefore a potential therapeutic target. Highlights: We generated the knockdown of PRPF4 gene in breast cancer cell line for function study. Knockdown of PRPF4 decreased the proliferation and colony formation of breast cancer cells. Knockdown of PRPF4 increased apoptosis of breast cancer cells. Knockdown of PRPF4 decreased migration, invasion and epithelial mesenchymal transition ability of breast cancer cells. Knockdown of PRPF4 regulates breast cancer cells progression by decreasing p38 MAPK signaling pathway.